Hubungan Rasio Camel dengan Return Saham pada Perusahaan Perbankan di Bursa Efek Indonesia - Muammar Khaddafi; Ghazali Syamni (Jurnal Aplikasi Manajemen, 2011)
This study aimed to analyze the relationship CAMEL ratios with stock returns on the banking company in the Indonesia Stock Exchange. Data used in this research is secondary data in the form of 21 financial reports of 29 banking companies in Indonesia Stock Exchange. This study uses multiple regression analysis method to analyze the data. The results found that the presence of a strong correlation between independent variabel CAR, NPL, PPAP, FBI, ROA, ROE, LDR, BOPO, and NIM with the dependent variable stock return that is equal to 70.6. These findings indicate that 70.6% stock return variation returs explaining about the relationship with stock return. Research has found that all variables simultaneously associated with stock return, but partially this research found that these variables have a significance level of diverse, ROE and NIM and only one variable with significance level of 5% ie LDR variables. This means that all four variables are partially related significantly to stock returns. Based upon the findings of this study indicate that investors in investing in banking stocks in particular to pay attention to the CAR, ROE, NIM and LDR company compared with other variables.Keywords: Analysis, CAMEL, Indonesian Stock Exchange